Optimizing an Octane Number of Motor Gasoline (MOGAS) 91 RON with Blending Methods - Ahmad Mustafid Miftahul Huda; Subagjo Wakimin; Selvia Sarungu (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Motor Gasoline (MOGAS) that serves as modifiers thermal energy into mechanical energy with a Research Octane Number (RON) of 91 was produced by mixing (blending) of two components. RON are high is one of MOGAS specifications needed for good engine performance. To obtain a MOGAS with high RON usually needs additional materials, chemical components. In this work we don’t need any additional materials to increasing the RON. In the field of oil and gas blending method is a method that is widely used to acquire new products that are superior and achieve quality standards. The components used in blending these are products with a value of RON 88 and 92. Examination of specific gravity (ASTMD-1298) was conducted to obtain specific gravity (SG) and temperature observations (T), while the ASTMD-86 distillation examination was conducted to determine the components in materials. The results showed that the product specifications in accordance with the existing products on the market. The acquisition of distillate reached 95% with losses of about 3.9%, and the residue of 1.1%.